The Tübingen School’s interpretation of Plato, presented epistemologically as a “Hermeneutical Paradigm” alternative to the currently dominant one - Reale, Giovanni (Revista Archai, 2011)
This text is, first, on the interpretation of Plato inaugurated by Tübingen’s School of interpretation of Plato, explaining how this school, with accurate historical trait, takes into account the specificity of cultural revolution in progress at the time of Plato. In sequence, it explains the reasons that motivated the author of this paper, some years ago, to make a replay of the new interpretation of Plato. This paper brings forth an important opinion of Hans Krämer about this replay. Finally, comments are made on publications from the eighties until now on Plato and the history of Platonism, and on recent theoretical contributions in defense of the new paradigm of reading the works of Plato.